Arab-market penetration by small firms through localized website (Journal of Business Management and Accounting, 2012)
Indigenous small firms going international, in particular to the Arab-markets, often face many difficulties and many have failed at the early stage. The modern technology also seems to be of less help as these firms are struggling to compete with their larger counterparts. The paper highlights the preference of the local Arab people (Jordanian) on the localized websites and such preference can be used as the guide for small firms as the means to penetrate the Arab market as the localized website is found to significantly contribute to the higher acceptance level of the local people in Jordan as the source of information. The findings being revealed in the paper is based on the study on the effects of culture and language of the website on user acceptance. The research was conducted in mid-2010 using quantitative method by adopting the cluster sampling technique. This insight provides crucial information and could be the platform for the success of small firms in penetrating the Arab markets.